INFLUENCE OF GREENHOUSE SHADING AND DIFFERENT NUTRIENT MANAGEMENT PRACTICES ON ALLEVIATING HEAT STRESS, IMPROVING PLANT NUTRIENTS STATUS, FLOWERING GROWTH AND YIELD OF TOMATO - & Sadiq, Sulaiman (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2020)
The experiment was conducted in a greenhouse during 2017 and 2018 growing seasons to evaluate the impact of the shading and various nutrition programs on mitigating heat stress, reducing the use of chemical minerals, improving the reproductive growth and yield of tomato plant. Split-plot within Randomized Complete Block Design (RCBD) with three replications was conducted in this study. Shading factor was allocated in the main plots and the nutrition programs distributed randomly in the subplots. Results indicate that shading resulted in the decrease of daytime temperature by 5.7˚C as an average for both seasons; thus a significant increasing was found in leaf contents of macro nutrients (Nitrogen, Phosphorous, and Potassium), and micro nutrients (Iron, Zinc and Boron), except the Iron content in 2018 growing season. Furthermore, shading improved significantly the reproductive growth and tomato yield. Among the plant nutrition programs, the integrated nutrient management (INM) including the application of organic substances, bio inoculum of AMF and 50% of the recommended dose of chemical fertilizers; lead to the enhancement of nutrients content, reproductive characteristics and plant yield. Generally, combination of both shading and INM showed positive effects on plants nutrient status and persisting balance on tomato flowering growth and fruits yield.